Prostate fibroblasts enhance androgen receptor splice variant 7 expression in prostate cancer cells. Issue 4 (7th December 2022) - Sasaki, Takeshi; Yoshikawa, Yumi; Kageyama, Takumi; Sugino, Yusuke; Kato, Manabu; Masui, Satoru; Nishikawa, Kouhei; Inoue, Takahiro
Abstract: Background: Androgen receptor splice variant (AR‐V) expression has been associated with prostate cancer (PCa) progression to castration‐resistant PCa during androgen deprivation therapy, which reduces androgen production and inhibits androgen action in PCa cells. However, the mechanisms whereby aberrant AR‐V expression is increased in PCa are still largely unknown. Fibroblasts in tumor stroma influence PCa initiation and aggressiveness, and which may play a crucial role in eliciting genetic changes during malignant transformation in human prostate epithelium. Here, our aim was to determine whether prostate fibroblasts in tumor stroma induce aberrant AR‐V7 expression in PCa cells under low androgen concentration. Methods: We performed in vitro experiments using androgen‐sensitive, AR‐positive PCa cell lines (LNCaP and 22Rv1 cells), commercially available prostate stromal cells (PrSC), and primary cultured prostate fibroblasts (pcPrF) from PCa specimens collected from biopsies of patients with advanced PCa. PCa cells were cocultured with each of the three fibroblast lines (PrSC, pcPrF‐M37, and pcPrF‐M48). Results: The proliferation under low androgen concentration of LNCaP and 22Rv1 cells cocultured with PrSC, pcPrF‐M37, or pcPrF‐M48 was significantly increased compared to that of PCa cells cultured alone. Androgen receptor‐full length (AR‐FL) protein expression was increased in LNCaP and 22Rv1 cells cocultured with PrSC, pcPrF‐M37, or pcPrF‐M48. AR‐V7 protein expression was increased in 22Rv1 cells cocultured with PrSC, pcPrF‐M37, or pcPrF‐M48. Under low androgen concentration, AR‐V7 protein expression was slightly detected in LNCaP cells cocultured with PrSC or pcPrF‐M37. Cytokine array analysis revealed that monocyte chemotactic protein‐1 (MCP‐1) and interleukin‐8 (IL‐8) levels in the conditioned medium of 22Rv1 cells cocultured with PrSC, pcPrF‐M37, or pcPrF‐M48 were increased under low androgen concentration. High IL‐8 concentration (30 ng/ml) resulted in significantly increased protein expression of AR‐FL, AR‐V7, and phospho‐NF‐κB p65 in 22Rv1 cells. In contrast, IL‐8 antibody (1 µg/ml) decreased AR‐V7 protein expression in 22Rv1 cells cocultured with PrSC, pcPrF‐M37, or pcPrF‐M48. Conclusions: pcPrF from PCa specimens increase the expression of aberrant AR‐V7 in PCa cells. IL‐8 may be a target for preventing the expression of aberrant AR‐Vs in PCa.